2006
DOI: 10.1007/s11104-006-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the PNM Model for Simulating Drain Flow Nitrate-N Concentration Under Manure-Fertilized Maize

Abstract: Mathematical models may be used to develop management strategies that optimize the use of nutrients from complex sources such as manure in agriculture. The Precision Nitrogen Management (PNM) model is based on the LEACHN model and a maize N uptake/growth and yield model and focuses on developing more precise N management recommendations. The PNM model was evaluated for simulating drain flow nitrate-nitrogen (NO 3 -N) in a 3-yr study involving different times of liquid manure application on two soil textural ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Adapt-N's underlying soil model, LEACHN, has been extensively tested Jemison et al, 1994;Sogbedji et al, 2001aSogbedji et al, , 2006. The crop subroutines were developed as reported in Muchow and Sinclair (1991), Muchow et al (1990), Sinclair and Amir (1992), and equations and validation are presented in Sinclair and Muchow (1995).…”
Section: Adapt-nmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapt-N's underlying soil model, LEACHN, has been extensively tested Jemison et al, 1994;Sogbedji et al, 2001aSogbedji et al, , 2006. The crop subroutines were developed as reported in Muchow and Sinclair (1991), Muchow et al (1990), Sinclair and Amir (1992), and equations and validation are presented in Sinclair and Muchow (1995).…”
Section: Adapt-nmentioning
confidence: 99%
“…The crop subroutines were developed as reported in Muchow and Sinclair (1991), Muchow et al (1990), Sinclair and Amir (1992), and equations and validation are presented in Sinclair and Muchow (1995). The combined PNM model was tested by Sogbedji et al (2006) and and showed low prediction errors. Graham et al (2010) applied the model to generate within-field site-specific N recommendations.…”
Section: Adapt-nmentioning
confidence: 99%
“…In some areas of Africa, vegetable cropping systems such as maize and cowpea often are practiced (Mead and Willey, 1980). Some factors that will influence or not whether two crops can be successfully intercropped include plant height (Spiejer et al 2006), the size of the leaves and the orientation and distribution of these leaves in the plant canopy (Sogbedji et al 2006). These variables affect the amount of sunlight that passes through the canopies (Grossman and Quales, 1993), which could influence the photosynthetic rates of the leaves within the canopy.…”
Section: Vegetable Cropsmentioning
confidence: 99%
“…These variables affect the amount of sunlight that passes through the canopies (Grossman and Quales, 1993), which could influence the photosynthetic rates of the leaves within the canopy. In intercropping systems with different canopy heights the crop in the under story needs to be shade tolerant for the plant to be productive (Sogbedji et al, 2006).…”
Section: Vegetable Cropsmentioning
confidence: 99%
“…Data required by the PNM model to simulate crop residue mineralization include the total C (kg C ha -1 ) and total N (kg N ha -1 ) of the residue at termination. The C in the residue is mineralized using a first order rate equation and rate constants based on PNM model calibration studies (Sogbedji et al, 2006;Marjerison et al, 2016). Residue N is either released to the soil (net mineralization) or temporarily immobilized depending primarily on the residue C/N ratio.…”
Section: Estimating Nitrogen Mineralization From Cover Crop Mixturesmentioning
confidence: 99%